Endothelial Cell Inflammation and Antioxidant Capacity are Associated With Exercise Performance and Microcirculation in Patients With Symptomatic Peripheral Artery Disease. (October 2015) - Gardner, Andrew W.; Parker, Donald E.; Montgomery, Polly S.; Sosnowska, Danuta; Casanegra, Ana I.; Ungvari, Zoltan; Csiszar, Anna; Sonntag, William E.
We determined whether exercise performance and lower extremity microcirculation were associated with endothelial cell inflammation, oxidative stress, and apoptosis and with circulating biomarkers of inflammation and antioxidant capacity in 160 patients with symptomatic peripheral artery disease (PAD). In a multivariate regression model for peak walking time, significant independent variables included ankle–brachial index ( P < .001), age ( P = .017), hydroxyl radical antioxidant capacity ( P = .008), and endothelial cell nuclear factor K-light-chain-enhancer of activated B cells (NF-κB) activity ( P = .015). In multivariate analyses for time to minimum exercise calf muscle hemoglobin oxygen saturation (StO2 ), significant independent variables included endothelial cell NF-κB activity ( P = .043) and calf muscle StO2 at rest ( P = .007). Endothelial cell inflammation and circulating biomarkers of inflammation and antioxidant capacity were associated with exercise performance and microcirculation of the ischemic calf musculature during exercise. The clinical implication is that interventions designed to alleviate endothelial cell inflammation and circulating inflammatory biomarkers, such as antioxidant therapy, may improve exercise performance of symptomatic patients with PAD.